Presentation Effects in Cross-Cultural Experiments - An Experimental Framework for Comparisons - Sebastian J. Goerg; Gari Walkowitz (University of Bonn, Bonn Graduate School of Economics (BGSE), 2008)
This paper investigates the impact of game presentation dependent on ethnical affiliation. Two games representing the same logical and strategical problem are introduced. Presented games are continuous prisoner's dilemma games where decision makers can choose an individual level of cooperation from a given range of possible actions. In the first condition, a positive transfer creates a positive externality for the opposite player. In the second condition, this externality is negative. Accomplishing a cross-cultural experimental study involving subjects from the West Bank and Jerusalem (Israel) we test for a strategic presentation bias applying these two conditions. Subjects in the West Bank show a substantially higher cooperation level in the positive externality treatment. In Jerusalem no presentation effect is observed. Critically discussing our findings, we argue that a cross-cultural comparison leads to only partially meaningful and opposed results if only one treatment condition is evaluated. We therefore suggest a complementary application and consideration of different presentations of identical decision problems within cross-cultural research.
Keywords: A13; C72; C91; F51; Z13; 330; Cooperation; presentation of decision problems; framing; methodology; crosscultural research; Gefangenendilemma; Kooperation; Kulturpsychologie; Test; Westjordanland; Jerusalem